Gut microbiota and metabolite profiles in HBV cirrhosis with persistent liver enzyme abnormalities - He, Huan; Zou, Ruixue; Liao, Xinyi; Lan, Yinghua (Frontiers in Microbiology, 2025)
Background and aimsDysbiosis of gut microbiota and metabolic disturbances are implicated in the progression of hepatitis B virus (HBV)-related cirrhosis. However, the mechanisms underlying these associations, particularly in patients with undetectable HBV-DNA following antiviral therapy but persistent liver enzyme abnormalities, remain poorly understood. This study aimed to characterize the gut microbiota and metabolic profiles in this patient population to elucidate potential mechanisms and identify biomarkers.Materials and methodsSixty-five patients with HBV-related cirrhosis were enrolled. Fecal samples were analyzed using 16S rRNA gene sequencing and untargeted liquid chromatography-mass spectrometry (LC–MS) to assess gut microbiota composition and metabolite profiles. Correlation analyses and multivariate statistical approaches were employed to explore relationships between microbiota, metabolites, and clinical parameters.ResultsSignificant gut microbiota dysbiosis was observed in HBV-related cirrhosis patients. Comparative analysis identified 15 differentially abundant genera and 431 metabolites between patients with normal and abnormal liver enzyme levels. Notably, Blautia abundance was positively correlated with ursocholic acid (UCA), which was significantly reduced in patients with abnormal liver enzymes. UCA levels were inversely associated with AST, TBIL, and ALP, suggesting its potential role in modulating liver enzyme activity.ConclusionThese findings highlight the gut-liver axis as a driver of persistent liver injury and identify microbial (e.g., Blautia) and metabolic (e.g., UCA, TDC) signatures as potential biomarkers for HBV cirrhosis.